Analysis of Velocity dispersion and Attenuation in Double-scale Model. Issue 3 (February 2021) - Zhou, Dan; Sun, Zhentao
Abstract: In the two states of oil-gas and water-gas, the wave velocity and attenuation coefficient are numerically simulated by double-scale model. The P-wave velocity and attenuation coefficient curves show double-step and double-peak, respectively. With the increase of gas saturation, the velocity step of mesoscopic scale gradually decreases and disappears. The attenuation peak decreases and the characteristic frequency shifts to high frequency until it coincides with the characteristic frequency of the micro-scale. The superposition of the attenuation peak makes the total attenuation peak increase. And there is a great difference in fluid properties when oil, gas and water are mixed in the reservoir, so the double-scale model can better predict the fluid saturation in the reservoir and better monitor the fluid.